Candidemia Following Ureteric Stent Placement in a Patient With Type 2 Diabetes Treated With Canagliflozin - Raj, Rishi; Hendrie, Jon; Jacob, Aasems; Adams, Derick (Frontiers in Endocrinology, 2019)
A 38-year-old female patient with well-controlled type II diabetes mellitus treated with canagliflozin underwent ureteral stent placement for obstructive renal calculi. Ten days following ureteroscopy and ureteral stenting, she developed fevers and blood cultures grew Candida glabrata (C. glabrata). The patient was successfully treated with an extended course of broad-spectrum antibiotic and antifungal agents. The clinical presentation of candidemia is nearly indistinguishable from bacteremia and can result in a delay in diagnosis and treatment. Candiduria is commonly seen in diabetic patients however it rarely leads to candidemia in an otherwise healthy person following relatively simple urologic procedures. Sodium-glucose co-transporter 2 (SGLT-2) inhibitors act by its glycosuric effect and further increases the risk of genitourinary candida infection. Urologic procedures can lead to bloodstream entry of the genitourinary fungal organisms and result in life-threatening fungemia. We report a case of candidemia in a diabetic patient on SGLT-2 inhibitors following ureteric stent placement to emphasize the need for awareness of this potentially fatal condition especially with a delay in diagnosis.